Sobre a unidade do Protágoras de Platão - Joao Paulo de Oliveira Teixeira (2015)
This dissertation argues in favor of the unity of Plato´s Protagoras, taking as reference the dispute concerning 'education'. The dialogue articulates several argumentative levels: the speech in favor of the possibility of teaching virtue, the debate over the unity of virtues, the discussion of Simonides´ poem and the Socratic defense both of hedonism and of intellectualism. We propose to articulate the dialogue´s different parts in such a way as to show that it should be recognized as one of Plato´s great first phase dialogues. The denial of the possibility of teaching virtues on the part of Socrates, if understood in an articulated way with the thesis that virtue is something divine and unattainable by humans, anticipates the theme of philosophy, not as pre established knowledge (which is the conception sophistry makes of itself), but as a disposition of the soul for knowledge, understood as 'love of knowledge'. Likewise, hedonism and intellectualism, if read in an articulated way, anticipate the Republic´s theory of action and open the way to further determination of the field of knowledge that is specific to the philosopher: he is not interested in the impossible knowledge of all human things and activities, but rather in offering a better and more human life, providing, at the same time, more pleasure and more rationality.